The subject and the methods of vandalism - Латиш, К. В. (Problems of legality, 2013)
This article deals with the problems of improving the efficiency of opposition to vandalism and other offenses against public order. We investigate the meaning of the term "vandalism", its definition in the criminal law of other countries, the subject of a criminal assault is formulated and how it occurred.